Design of a photovoltaic system for Pinturas y Ferretería H. Barón S.A.S. (2025)
The company Pinturas y Ferretería H. Barón S.A.S has experienced numerous days of operational instability due to interruptions in the electrical supply. Additionally, it has faced high energy supply costs, making it necessary to reduce dependence on the conventional power grid and implement an alternative electricity supply. An off-grid photovoltaic system was designed, independent of the grid and fully autonomous, to operate throughout the entire workday and power critical devices. To achieve this, an energy analysis and site evaluation were conducted, including a shadow and location analysis to calculate solar irradiation, the potential energy captured, and the optimal tilt angle and orientation of the panels. The off-grid system consists mainly of solar panels with a ground-mounted support structure, batteries, a charge controller, and an inverter. Several engineering standards were applied, primarily the Technical Regulation of Electrical Installations (RETIE) and the Colombian Technical Standard NTC 2050 - Section 690: Photovoltaic Solar Energy. Additionally, a budget was prepared for the construction of the system, expressed in Colombian pesos. A maintenance plan was also developed based on IEEE and IEC standards. Furthermore, by calculating the costs and benefits over the minimum lifespan of the solar panels, a cost-benefit ratio greater than 1 was obtained, indicating that the system will generate economic benefits for the company and effectively meet its needs. The system has been theoretically validated by an electrical engineer.